Repeated and multiple fecal microbiota transplantations plus partial enteral nutrition as the first-line treatment in active pediatric Crohn’s disease - Zou, Biao; Liu, Shengxuan; Li, Xuesong; He, Jiayi; Dong, Chen; Ruan, Mengling; Huang, Zhihua; Shu, Sainan (Frontiers in Cellular and Infection Microbiology, 2023)
Background Most studies have reported fecal microbiota transplantation (FMT) as an effective secondary option for Crohn’s disease (CD). However, there is little data on FMT as a first-line treatment for CD. In our study we explore the rates of clinical and endoscopic remission and mucosal healing after FMT plus partial enteral nutrition (PEN), as a first-line treatment for active CD in children. Methods We retrospectively enrolled pediatric CD patients who underwent PEN or PEN plus FMT treatment at diagnosis from November 2016 to July 2019 at the Pediatric Department, Tongji Hospital. The two groups were defined as FMT group (repeated and multiple doses of FMT plus PEN) or PEN group (PEN alone). All the patients received PEN intervention. At baseline and week 8- 10, the FMT group was administered multiple doses of FMT to help induce and maintain remission. All patients were evaluated at week 8- 10 and 18-22 via clinical and relevant laboratory parameters and endoscopic results. The clinical and endoscopic remission and mucosal healing rates were compared between the two groups at different time points after the therapy. Results Twenty-five newly diagnosed active CD patients were included in the study, containing 7 females and 18 males with a median age of 11. 1 ± 2.3 years. 13 and 12 patients were assigned to the PEN and FMT groups, respectively. At week 8-10, clinical remission was obtained in 83.3% and 53.8% of the FMT and PEN groups, respectively (p=0.202). The endoscopic remission rates were 72.7% for FMT and 25.0% for PEN (p=0.039), whereas the mucosal healing rates were 27.2% for FMT and 0% for PEN (p=0.093). At week 18-22, clinical remission was achieved in 72.7% and 20.0% of patients in the FMT and PEN groups, respectively (p=0.03). Theendoscopic remission rates were 66.6% and 12.5% in the FMT and PEN groups, respectively (p=0.05), whereas the mucosal healing rates were 55.5% and 0% in FMT and PEN groups, respectively (p=0.029). Conclusion This study demonstrate that FMT plus PEN can be used as a first-line treatment for active CD in children.